Chemistry And Applications Of Nano Composites: An Update About Recent Developments - Zunaira Nasir; Arooj Fatima; Rana Mohsin Ali (International journal of technology and education research, 2023)
Nano materials can be defined as materials possessing, at minimum one external dimension measuring 1-100nm. They include Nano particles, nano fibers, nano suspensions, nano emulsuions, quantum dots and nano composites. Nanocomposite is a multiphase solid material where one of the phases has one, two or three dimensions of less than 100 nanometers or structures having nano- scale repeat distance between the different phases that make up the material. Nano composites are of two types: polymer-based nanocomposites and non-polymer-based nanocomposites.Polymer nanocomposites (PNC) consist of a polymer or copolymer having nanoparticles or nanofillers dispersed in the polymer matrix.Non-polymer-based nanocomposites are also known as inorganic nanocomposites. They can be further classified into metal-based nanocomposites, ceramic-based nanocomposites, and ceramic-ceramic-based nanocomposites. Nano composites can be prepared by in situ polymerization, melt mixing, solution mixing, precipitation, sol-gel process and electrospinning. They can be characterized by scanning electron microscopy, transmission electron microscopy, X- ray diffraction, Fourier-transform infrared spectroscopy and thermogravimetric analysis. Nanocomposites have been growing with a speedy rate so as their large number of applications. In the next 10 years, the worldwide production will exceed 600,000 tons in the following regions: Superior strength fibers and films, UV protection gels, drug delivery systems, new fire-retardant materials, anti-corrosion barrier coatings, lubricant and stretch paints.